Performance and emission evaluation of diesel engines using Karanja biodiesel blended with diethyl carbonate - Bhavin Mehta; Abhishek Swarnkar; Dattatraya Subhedar (Results in Engineering)
This research investigates the application of Diethyl Carbonate (DEC) as an oxygenated additive in Karanja biodiesel (B20) fuel blends to promote combustion performance and decrease emissions in a compression ignition engine. Different from frequently researched additives like DEE, ethanol, or DMC, DEC possesses a special set of characteristics with high cetane number, high oxygen content, and low volatility, promoting complete combustion with lower peak flame temperatures. Experimental findings revealed that a 10 % DEC blend provided 6.5 % better brake thermal efficiency and 7.8 % lower BSFC than B20. NOx, CO, HC, and smoke emissions reduced by 13 %, 29.8 %, 24.5 %, and 42.5 %, respectively. These gains indicate that DEC does not only avoid the common NOx–particulate trade-off but also maximizes fuel economy without sacrificing engine operation. An initial carbon footprint analysis approximated a yearly CO₂ savings of 382.22 kg per engine. Although this is indicative of future carbon credit possibilities, techno-economic evaluation at a scale is needed to assess full-scale viability. On the whole, the results suggest that DEC-upgraded biodiesel blends provide a promising avenue toward stricter emissions compliance and greater adoption of sustainable biofuels.